Using Backwards Generated Goals for Heuristic Planning - Alcázar, Vidal; Borrajo, Daniel; Linares López, Carlos (Proceedings of the International Conference on Automated Planning and Scheduling, 2010)
Forward State Planning with Reachability Heuristics is arguably the most successful approach to Automated Planning up to date. In addition to an estimation of the distance to the goal, relaxed plans obtained with such heuristics provide the search with useful information such as helpful actions and look-ahead states. However, this information is extracted only from the beginning of the relaxed plan. In this paper, we propose using information extracted from the last actions in the relaxed plan to generate intermediate goals backwards. This allows us to use information from previous computations of the heuristic and reduce the depth of the search tree.